Growth Intermediates for CVD Graphene on Cu(111): Carbon Clusters and Defective Graphene - Niu, Tianchao; Zhou, Miao; Zhang, Jialin; Feng, Yuanping; Chen, Wei (Journal of the American Chemical Society, 2013)
Graphene growth on metal films via chemical vapor deposition (CVD) represents one of the most promising methods for graphene production. The realization of the wafer scale production of single crystalline graphene films requires an atomic scale understanding of the growth mechanism and the growth intermediates of CVD graphene on metal films. Here, we use in situ low-temperature scanning tunneling microscopy (LT-STM) to reveal the graphene growth intermediates at different stages via thermal decomposition of methane on Cu(111). We clearly demonstrate that various carbon clusters, including carbon dimers, carbon rectangles, and ‘zigzag’ and ‘armchair’-like carbon chains, are the actual growth intermediates prior to the graphene formation. Upon the saturation of these carbon clusters, they can transform into defective graphene possessing pseudoperiodic corrugations and vacancies. These vacancy-defects can only be effectively healed in the presence of methane via high temperature annealing at 800 °C and result in the formation of vacancy-free monolayer graphene on Cu(111).